Effects of Inqury Method on Students’ Attitude in Learning English Language in Kumo, Gombe State - Waziri, Ahmed Muhammad; Waziri, Mohammed Bularafa; Tilde, Isa Abdulkarim; Aliyu , Dahiru (Kashere Journal of Education, 2025)
The study on the Effects of the inquiry method of teaching on students' attitudes in learning the English Language in Kumo, Gombe state, Nigeria, was specifically determined to find out the pretest and posttest English Language Students’ attitudes towards English Language learning. The research work sought to find out if there was a significant difference or no significant difference in the students’ attitude in the English Language when taught using the inquiry-based method of teaching techniques. This research work had one objective with one corresponding research question and hypothesis. The duration of the research work was ten weeks. The scope of this study was on the effects of the inquiry method of teaching, which specifically focuses on Listening and Speaking Skills on students’ attitudes. The Students' English Language Attitude Scale (SELAS) was designed and administered to both the control and experimental groups. A total of 155 students participated in the study. Experimental group was made of 82 students, while the control group was 73 students. The analysis of the data collected was done using appropriate tools in Statistical Package for Social Sciences (SPSS) 20th Edition. The study finds out that students taught English Language in SS II using the inquiry-based method performed better than those taught using the conventional method.